2000
DOI: 10.1680/macr.2000.52.6.443
|View full text |Cite
|
Sign up to set email alerts
|

Proposed changes to flexural design in BS 8110 to allow over-reinforced sections to fail in a ductile manner

Abstract: The provisions for flexural design contained in BS 8110 have been reviewed in the context of introducing improvements in the level of ductility that can be achieved in structural concrete sections. Increased ductility will lead to corresponding enhancements in the flexural behaviour of members. Accordingly, changes to the present approach to flexural design in this code have been put forward. Design equations have been developed and compared to those present in the code. The proposed approach permits a section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 2 publications
1
10
0
Order By: Relevance
“…The comparison between the effect of helix with rectangular confinement of over reinforced concrete beams using the experimental data of Mansur et al [9] and Ziara et al [10] The results of the tests in this study correlate very well with other tests done and reported, for example [3,[11][12][13].…”
Section: Comparison Between Helix and Tie Confinementsupporting
confidence: 86%
“…The comparison between the effect of helix with rectangular confinement of over reinforced concrete beams using the experimental data of Mansur et al [9] and Ziara et al [10] The results of the tests in this study correlate very well with other tests done and reported, for example [3,[11][12][13].…”
Section: Comparison Between Helix and Tie Confinementsupporting
confidence: 86%
“…Also the beams, which have longitudinal compression reinforcement, suffer from early failure because of the compression reinforcing buckling problem. Furthermore Mansur et al [7] and Ziara et al [8] found that the mid-span displacement ductility of beams enhanced significantly by using rectangular tie confinement. As a result of the experimental program conducted by Shah and Rangan [6], which proved that providing confinement in the compression zone of the beam is more efficient than providing steel fibres or compression longitudinal reinforcement.…”
Section: The Efficiency Of Helical Confinementmentioning
confidence: 99%
“…However, that is proved experimentally that the helix is more effective than the rectangular ties for NSC by [15]. The comparison between the effect of helix with rectangular confinement of over reinforced concrete beams using the experimental data of Mansur et al [17] and Ziara et al [12] was very difficult because of different variables such as size and span of the beam, tie spacing and longitudinal reinforcement ratio. The comparison between the effectiveness of helix and tie in the compression zone of HSC beams will be undertaken during the next stage of the extensive experimental program at the University of Wollongong [15].…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%